Academic boredom and its relationship to cooperative learning For middle school students (Journal of the College of Basic Education, 2024)
The research aims to identify the level of:1- Academic boredom among middle school students.2 - Differences in academic boredom according to the gender variable (males, females) among middle school students.3- Cooperative learning among middle school students.4 - Differences in cooperative learning according to the gender variable (males, females) among middle school students.5- The relationship between academic boredom and cooperative learning among middle school students. The research community was chosen from fifth grade students from middle schools in the city of Baghdad for the academic year 2022-2023.The researcher adopted the Academic Boredom Scale (by researcher Al-Aboudi 2020), and the Cooperative Learning Scale was built, and their validity and reliability were confirmed. The search results showed: 1- Preparatory school students suffer from academic boredom. There were differences in gender in favor of males, meaning that they were more bored academically than females.2- Preparatory school students do not want cooperative education, and there are no differences in gender.3 - There is a positive correlation between academic boredom and cooperative learning among middle school students. The researcher presented recommendations and suggestions.